Volcanostratigraphic Sequences of Kebo-Butak Formation at Bayat Geological Field Complex, Central Java Province and Yogyakarta Special Province, Indonesia - Sri Mulyaningsih (Indonesian Journal on Geoscience, 2016)
DOI:10.17014/ijog.3.2.77-94Bayat Complex is usually used as a work field for students of geology and other geosciences. The study area is located in the southern part of the Bayat Complex. Administratively, it belongs to Central Java Province and Yogyakarta Special Province. The lithology of Bayat is very complex, composed of various kinds of igneous, sedimentary, metamorphic, and volcanic rocks. Most of previous researchers interpreted Bayat as a melange complex constructed within a subduction zone. Kebo-Butak is one of formations that forms the Bayat field complex. The formation is composed of basalt, layers of pumice, tuff, shale, and carbonaceous tuff. Most of them are known as volcanic rocks. These imply that volcanic activities are more probable to construct the geology of Bayat rather than the subducted melange complex. The geological mapping, supported by geomorphology, petrology, stratigraphy, and geological structures, had been conducted in a comprehensive manner using the deduction-induction method. The research encounters basalt, black pumice, tuff with basaltic glasses fragments, zeolite, argilic clay, as well as feldspathic- and pumice tuff. Petrographically, the basalt is composed of labradorite, olivine, clinopyroxene, and volcanic glass. Black pumice and tuff contain prismatic clinopyroxene, granular olivine, and volcanic glasses. Feldspathic tuff and pumice tuff are crystal vitric tuff due to more abundant feldspar, quartz, and amphibole than volcanic glass. Zeolite comprises chlorite and altered glasses as deep sea altered volcanic rocks. The geologic structure is very complex, the major structures are normal faults with pyrite in it. There were two deep submarine paleovolcanoes namely Tegalrejo and Baturagung. The first paleovolcano erupted effusively producing basaltic sequence, while the second one erupted explosively ejecting feldspathic-rich pyroclastic material. The two paleovolcanoes erupted simultaneously and repeatedly.